Correlation Between Lipid Profile and Liver Function in Patients With Non-Alcoholic Fatty Liver - A'laa H. Juwad; Ammar L. Hussein (Diyala Journal of Medicine, 2024)
Background: Non-alcoholic fatty liver disease (NAFLD) is a metabolic liver disease characterized by a broad range of liver pathology, including simple steatosis, steatohepatitis (NASH), fibrosis, cirrhosis, and hepatocarcinoma. NAFLD has emerged as a public health concern in the world within the last 20 years, it is linked to metabolic syndrome (MetS), type 2 diabetes mellitus (T2DM), obesity, and dyslipidemia. Increased visceral adipose tissue in obese people can cause insulin resistance (IR) and hyperinsulinemia, which will speed up the lipolysis of adipose tissue, Lipo-toxicity-related chronic low-grade inflammation is involved in the development of NAFLD. Objective: Determine the correlation between lipid profile and liver function in patients with NAFLD. Patients and Methods: A study was conducted at Tikrit Teaching Hospital from 28 November to 28 December 2023. The study involved 90 participants, 60 with NAFLD and 30 healthy subjects. The study used a spectrophotometer (Model NO. HV-2800EX) and a colorimetric kit from Spain linear chemicals to determine various parameters, such as Aspartate aminotransferase (AST), Alanine aminotransferase(ALT), Gamma-glutamyl transferase(GGT), High-density lipoprotein(HDL), Low-density lipoprotein(LDL), Very low-density lipoprotein(VLDL), Triglyceride(TG), and cholesterol. Results: The mean age of patients in the group was 40.93 years, with ages ranging from 20 to 50 years. Serum levels of liver function enzymes (GGT, AST, ALT) and lipid profile (TG, HDL, LDL, VLDL, cholesterol) were measured and compared to the control groups. Patients with NAFLD had significantly higher serum liver function enzymes and increased serum lipid profile (TG, VLDL, LDL, and cholesterol) while showing a significant decrease in HDL concentration when compared to the control group. Conclusion: The patients showed an increase in liver function enzymes (AST, ALT, GGT) and lipid profile (LDL, VLDL, TG, cholesterol) with reduced HDL as compared to healthy individuals. Keywords: Nonalcoholic fatty liver, liver function enzymes, lipid profile.